CURRENT STATUS OF JOB SATISFACTION AMONG HEALTHCARE WORKERS AT THUAN AN REGIONAL MEDICAL CENTER, HO CHI MINH CITY, IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe job satisfaction among healthcare workers at Thuan An regional Medical Center, Ho Chi Minh city, in 2025 and to identify associated factors.Subjects and methods: A descriptive cross-sectional study was conducted among 344 healthcare workers employed at Thuan An regional Medical Center from October to December 2025. Data were collected using a structured questionnaire assessing six domains: satisfaction with the working environment; direct supervisors and colleagues; internal regulations, salary, and benefits; job characteristics, learning opportunities, and career advancement; overall satisfaction with the medical center; and overall job satisfaction.Result: The overall job satisfaction score was 4.12 out of 5, with 68.9% of healthcare workers reporting satisfaction across all five surveyed domains. The highest satisfaction was observed for direct supervisors and colleagues (83.43%, mean score 4.20), while the lowest was related to internal regulations, salary, and benefits (72.97%, mean score 4.06). Length of service, professional specialty, and scope of work were significantly associated with job satisfaction (p < 0.05).Conclusion: Overall job satisfaction among healthcare workers at Thuan An regional Medical Center reached 68.9%. Targeted interventions are needed to improve job satisfaction, thereby enhancing work motivation, reducing staff turnover, improving patient care effectiveness, and strengthening healthcare service quality.
Keywords: Job satisfaction, healthcare workers, Thuan An regional Medical Center.